Economic growth with environmental hurdles in Uzbekistan: testing the EKC hypothesis - Nuriddinova, Maftuna; Ahmad, Maaz (Frontiers in Environmental Science, 2025)
Understanding the concept of the Environmental Kuznets Curve (EKC) is crucial for analyzing how environmental degradation evolves with economic growth, particularly as economies transition from low-income to high-income stages. However, Uzbekistan is a developing country undergoing rapid industrialization. Therefore, it is important to investigate whether the EKC hypothesis provides valuable insights into the intricate relationship between carbon emissions and economic growth. This study examines the applicability of the EKC hypothesis in Uzbekistan using the vector autoregression (VAR) model. Key variables selected for the analysis include CO2 emissions, GDP per capita, globalization, foreign direct investment, population density, corruption, and the square of GDP per capita. The study utilizes quarterly data spanning from Q3 1996 to Q4 2022. The results reveal a complex relationship between economic growth and CO2 emissions in Uzbekistan, partially supporting the EKC hypothesis. The results show a positive relationship between GDP per capita and CO2 emissions in Uzbekistan. Furthermore, the statistically significant coefficient of the squared GDP per capita term supports the EKC hypothesis, suggesting that Uzbekistan may have reached the EKC turning point. This indicates short-term environmental challenges associated with the early stages of economic growth and industrialization. In contrast, the findings suggest enhancing the role of government institutions and implementing effective policy measures, such as promoting green legislation and renewable energy sources. Additionally, the study emphasizes the importance of raising public awareness and improving education to foster green initiatives among the population.